Beginning the Mahabharata : a reader's guide to the frame stories - Earl, James Whitby (South Asian Studies Association, 2011)
This is a reader's guide to the prefatory materials, or preamble, which come before the main story begins, which include two interlocking frame stories. At 5,000 lines, it is a fraction of the whole poem, and this guide/explication to it ends at the beginning of the main narrative.